What characterizes first-time use of eldercare? A SNAC Stockholm Eldercare registry-based study of older people’s health and care needs in Sweden - Pernilla Alencar Siljehag; Åsa von Berens; Bettina Meinow; Carin Lennartsson; Janne Agerholm (BMC Health Services Research, 2026)
Abstract Background As populations age, it is becoming more important than ever to understand how older people’s care needs can be met and to ensure that local care providers are coordinated effectively. Describing older adults’ demographic characteristics, functional status, health status, and patterns of healthcare use leading up to their first-time use of eldercare provides valuable knowledge. This can facilitate the mobilization of expertise and methods in eldercare and healthcare and contribute to the joint planning of proactive and more targeted interventions for older adults. Methods Data on demographics and functional status of people ≥ 65 years in first-time eldercare (July 2021 to June 2022; n = 3649) were obtained from the SNAC Stockholm Eldercare study and combined with registry data on medical diagnoses and use of inpatient and outpatient care six months preceding eldercare entry. Data were summarized using descriptive analyses. The RECORD checklist was used as a reporting guide. Results The average age was 80 years. More than half were women and lived alone. One in four people had developed extensive functional limitations. Multimorbidity was common (92%) and almost half had as many as seven or more chronic conditions. Psychiatric comorbidity was prevalent in 15% of cases. Most people received informal care on a weekly or daily basis. Primary care was the predominant form of outpatient care, used by 80% of individuals before entering eldercare. The vast majority (95%) received home care. Every second person entered eldercare immediately following inpatient care. Many individuals in this group had experienced serious injuries, deterioration of existing chronic diseases or temporary infections. Conclusions Many older people enter eldercare with extensive and complex care needs and receive support and care from several providers. These findings highlight which needs and care contexts during the period preceding the first use of publicly funded eldercare services are particularly important to consider when developing timely and well-coordinated support. They are useful to guide collaborative strategies, facilitating the use of expertise and methods of both municipal and primary care actors.